Preconditions of Young Learners' Humanistic Education during Physical Education Lessons - Rolandas Jančiauskas (Lithuanian Sports University, 2018)
Research background and hypothesis. Favourable conditions for children's humanistic education will occur after the implementation of the programme of junior schoolchildren's humanistic education in physical education lessons. Research aim was to analyze the background for junior schoolchildren's humanistic education theoretically and to determine the tendencies of changes in the relationship between schoolchildren and teachers in physical education lessons. Research methods. Literature review and questionnaire survey. Research results. After the implementation of humanistic education program for junior schoolchildren in physical education lessons, their behavior became more humanistic, their relationship with classmates and teachers improved. Our ﬁ ndings coincided with those of the other authors. Junior schoolchildren's relationship particularly lack sensitivity. The ﬁ ndings of Group E have shown that children of that age group can already understand moral concepts and base their behavior on them. The experimental program had an effect not only on the behavior of children in Group E, but also on their teachers' behavior, which became more humanistic. Discussion and conclusions. Junior schoolchildren's education in a humanistic, safe and functional environment which fosters sincere relationship changed the relationship between pupils and teachers, so it can be assumed that the experimental program has proved to be successful in pedagogical practice. The study shows the changes of behavior of Group E teachers who participated in the educational experiment. Keywords: humanistic education, physical education lesson, relationship among junior schoolchildren.